Coping With Single Parenthood in Southwest Nigeria: Psychosocial Challenges and Adaptive Strategies Among Parents in Oye-Ekiti - Esther Adebimpe Ogunwole; Oladele Taiwo Omolara; Gbemisola Funmilayo Oguntola; Esther Opeyemi Abiodun (Department of Guidance and Counseling, FIP, Undiksha, 2026)
Single parents are increasingly common in developing societies and often face economic, psychosocial, social, and support-related challenges. Therefore, deeper understanding is needed of how they adapt to these conditions. This study aimed to analyze the psychosocial challenges experienced by single parents and examine the adaptive coping strategies they employ in navigating the demands of single parenthood. The study employed a quantitative survey research design involving 100 single parents selected as research participants. Data were collected using a structured questionnaire that measured psychosocial challenges, including stress, anxiety, and depression, as well as coping strategies related to economic engagement, personal character development, social image management, and family support. The collected data were analyzed using descriptive and inferential statistical techniques. The findings indicate that extended family support is the most dominant coping strategy, followed by efforts to build more positive social perceptions of single parents, engagement in productive economic activities, and strengthening personal resilience and moral values. The study concludes that single parents’ coping behavior is influenced by the interaction of cultural norms, economic conditions, and social demands. These findings imply the need to strengthen community-based support systems through counseling services, economic empowerment programs, stigma-reduction campaigns, and inclusive social welfare policies to improve the psychosocial well-being of single-parent families.